從壓迫到解放：南洋新移民女性自拍影片的反再現與實踐 From Oppression to Liberation: The Antirepresentation and Praxis of Self-filming among Female Immigrants from Southeast Asia - 柯妧青 Wan-Ching Ke (臺灣教育社會學研究, 2015)
本研究聚焦於近年來崛起的南洋新移民女性自拍行動， 以批判教育 （critical pedagogy）及女性主義（Feminism）電影理論為基礎，透過3位參與自拍的南洋新移民女性，以及她們的自拍影片文本，探究處於邊陲位置的「她者」，如何於影片製作過程進行自我探索與自我書寫，以及自拍學習行動能否幫助其自我解放。本研究發現，自拍學習幫助受壓迫的南洋新移民女性自我肯認與建構主體，透過觀景窗的自我映照，思考自己與世界的關係，完成一趟自我對話的生命旅程。若學習支持者能以批判教育的提問與對話方式啟發自拍者，有助其在影像敘事過程中建構批判意識，透過自我指涉影片改寫「我群」（wegroup）形象，以行動反抗主流文化再現。 Founded theoretically on critical pedagogy and feminist films, this study is centered on the contemporary action of “self-filming” among women who immigrated to Taiwan around 2000 from Southeast Asia for marital reasons. This paper investigates three Southeast Asian women and their selffilming video work to discover how marginalized “others” explore and represent themselves through the learning process of video-production and the text of their video-work, and to discover if the act of self-filming can help them to liberate themselves. The research findings reveal that self-filming helped these oppressed women acquire self-confidence and affirm their identity to construct their subjectivity. The Southeast Asian immigrant women went on a journey of self-exploration by looking at their self-reflections through the viewfinder of camcorder. The questioning and dialogues between the learners and the supporters of their learning during the image-narration process stimulated the oppressed immigrant women’s self-awareness, enabling them to construct their own critical consciousness. Thus, they became engaged in redefining their self-images through self-reflexive video work, effectively resisting existing representations within the mainstream culture.